(untitled) (GYMNASIUM, 2008)
After applying the theme games with reduced personnel on reduced terrain specific to the handball game in physical education lessons on high school pupils, the studied indicators were largely increased as opposed to the witness group, at which the teaching was applied with traditional methods.